Peningkatan Ketahanan Pangan Masyarakat Melalui Pelatihan Pembuatan Kembang Goyang Berbahan Dasar Sagu Di Kampung Baingkete - Masni Banggu; Miryam Diana Kalagison; Ana Lestari; Salmawati; La Basri; Mohamad Saleh Refra (LP3M Universitas Muhammadiyah Sorong, 2023)
The utilization of sago which is the result of local resources in Baingkete Village, Sorong Regency is still in the form of Papeda (rice substitute). The lack of knowledge and skills in sago management is still very low, while the availability of sago in Baingkete Village is quite a lot and can be of economic value. The purpose of this training activity is to provide knowledge and training in making sago-based rocking flower cakes. This activity was carried out in October 2021 in Baingkete Village, Makbon District, Sorong Regency. This activity requires several tools and ingredients for a rocking flower cake. Training activities for making sago-based rock flower cakes can increase knowledge about sago processing for the people of Baingkete Village. Kembang goyang cake made from sago is a cake variant that can be made by Papuan mothers as a snack in the family which can be an economical addition for small household businesses.